078 Chronic sleep and circadian disruption differentially affects blood pressure, renal sodium retention, and aldosterone secretion. (3rd May 2021) - McHill, Andrew; McMullan, Ciaran; Hull, Joseph; Wang, Wei; Klerman, Elizabeth
Abstract: Introduction: Chronic sleep restriction (CSR) and recurrent circadian disruption (RCD; e.g., rotating shiftwork) can increase an individual's risk of cardiovascular and kidney disease. However, no study has assessed whether CSR and RCD together increase blood pressure (BP) and alter renal function (RF). We tested the hypotheses that the combination of CSR and RCD would increase blood pressure, renal sodium retention, and aldosterone secretion in individuals living for 3 weeks on an imposed non-24-h sleep-wake (SW) schedule (induces RCD) and controlled diet with or without CSR. Methods: Seventeen (9M) healthy participants (aged 26.1±4.5y [mean±SD]) were scheduled to twenty-four 20-h Forced Desynchrony days and were randomized to either Control (1:2 sleep:wake, 6.67h sleep:13.33h wake; n=8) or CSR (1:3.3 sleep:wake, 4.67h sleep: 5.33h wake; n=9) SW conditions during a 32-day inpatient protocol. BP was measured following 80–90 min in constant seated posture after scheduled waketime. All urine voids were collected, combined and sampled in 3-6h blocks throughout the study. Samples were assayed for sodium, potassium and aldosterone and analyzed as both excretion rates and total secretion (both per 20h). Data were assigned circadian phase using fitted core body temperature and analyzed using mixed-effects models with circadian phase, aligned/misaligned sleep, or time awake (with associated scheduled activity, sleep/wake, and feeding behaviors) and their interactions as fixed effects. Results: There was a significant interaction between aligned/misaligned sleep and condition for resting BP (p=0.02), such that systolic BP was 6% higher following circadian-misaligned sleep in CSR compared to Control (p=0.04). Renal sodium and potassium followed a robust circadian pattern (p<0.0001), with limited influence of time awake. In contrast, the timing of aldosterone excretion was affected by time awake (p<0.05). Total daily renal sodium secretion decreased from beginning to end of the protocol (p=0.03), with no change in sodium consumption and aldosterone secretion (p=0.95). Conclusion: Under conditions similar to rotating shiftwork, systolic BP increased and sodium, potassium, and aldosterone were differentially influenced by circadian phase and scheduled behaviors. Additionally, renal sodium secretion decreased despite minimal changes in aldosterone secretion, suggesting increased renal aldosterone sensitivity. These findings may provide insight into mechanisms contributing to poor cardiovascular and renal health observed in shiftwork. Support (if any):